Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1159/000487084
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PD-1 Therapy Leads to Near-Complete Remission in a Patient with Metastatic Basal Cell Carcinoma

Abstract: Background: Metastatic basal cell carcinoma is rare and the prognosis is poor, with a lack of established treatment options for patients progressing on or after treatment with inhibitors of the hedgehog signaling pathway. Case Report: A man with pulmonary metastases of a basal cell carcinoma progressing after treatment with sonidegib and vismodegib was started on treatment with the anti-PD-1 antibody pembrolizumab. Upon treatment, rapid clinical improvement occurred, and after 5 cycles, the computed tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…Finally, we also envision that HH/GLI pathway blockers in combination with drugs targeting immune evasion mechanisms, such as immune checkpoint inhibitors, are likely to provide further therapeutic benefit. Although our present knowledge about the impact of HH/GLI on tumor immune evasion is fairly limited, first evidence from preclinical and clinical observations suggests that next-generation HH/GLI inhibitors together with strategies reactivating the antitumoral immune response may represent the next leap for anti-HH/GLI therapy of cancers [154,155,156,157,158].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we also envision that HH/GLI pathway blockers in combination with drugs targeting immune evasion mechanisms, such as immune checkpoint inhibitors, are likely to provide further therapeutic benefit. Although our present knowledge about the impact of HH/GLI on tumor immune evasion is fairly limited, first evidence from preclinical and clinical observations suggests that next-generation HH/GLI inhibitors together with strategies reactivating the antitumoral immune response may represent the next leap for anti-HH/GLI therapy of cancers [154,155,156,157,158].…”
Section: Discussionmentioning
confidence: 99%
“…To treat hedgehog inhibitor resistant tumours, immunotherapy is currently under investigation. There have been several case reports showing remarkable and sustained antitumour response with PD-1/PD-L1 blockade regardless of PD-L1 expression in vismodegib resistant BCC tumours 18 19…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, secondary resistance has been reported to be an HPI class-related effect, and a study in nine patients with advanced BCC resistant to vismodegib reported similar resistance with subsequent sonidegib treatment [31]. Off-label anti-programmed cell death protein 1 (PD-1) therapy showed promising results in case reports of patients with metastatic BCC that progressed or were resistant to previous HPI treatment [32,33], and anti-PD-1 agents (pebrolizumab, nivolumab, REGN2810) are currently under study for advanced BCC in clinical trials (NCT02690948, NCT03521830, NCT03132636). Recurrence after HPI discontinuation may occur, and in our clinical practice, we follow patients with response that discontinue HPI because of adverse events or personal reasons, every 3 months.…”
Section: Rechallenge With Hpimentioning
confidence: 99%